Research Progress and Application of PEO-Based Solid State Polymer Composite Electrolytes - Zhang, Danyang; Li, Lina; Wu, Xiaochao; Wang, Jun; Li, Qingkui; Pan, Kunming; He, Jilin (Frontiers in Energy Research, 2021)
As a high-efficiency energy storage and conversion device, lithium-ion batteries have high energy density, and have received widespread attention due to their good cycle performance and high reliability. However, currently commercial lithium batteries usually use organic solutions containing various lithium salts as liquid electrolytes. In practical applications, liquid electrolytes have many shortcomings and shortcomings, such as poor chemical stability, flammability, and explosion. Therefore, the liquid electrolyte has a great safety hazard. The use of solid electrolyte ensures the safety of lithium-ion batteries, and has the advantages of high energy density, good cycle performance, long life, and wide electrochemical window, making the battery safer and more durable, with higher energy density and simple battery Structural design. Solid electrolytes mainly include inorganic solid electrolytes and organic polymer solid electrolytes. Although both inorganic solid electrolytes and polymer solid electrolytes have their own advantages, as far as the existing research work is concerned, whether it is an inorganic system or a polymer system, a single-system solid electrolyte can never achieve the full performance of an ideal solid electrolyte. The composite solid electrolyte composed of active or passive inorganic filler and polymer matrix is considered as a promising candidate electrolyte for all-solid-state lithium batteries. Among many polymer systems, PEO-based is considered to be the most ideal polymer substrate. In this review article, we first introduced the structure, properties, and preparation methods of PEO-based polymer electrolytes. Furthermore, the researches related to the modification of PEO-based polymer solid electrolytes in recent years are summarized. The contribution of polymer structural modification and the introduction of additives to the ionic conductivity, electrochemical stability and mechanical properties of PEO-based solid electrolytes is described. Examples of different composite solid electrolyte design concepts were extensively discussed, such as inorganic inert nanoparticles/PEO, oxide/PEO, and sulfide/PEO. Finally, the future development direction of composite solid electrolytes was prospected.